Scholarly Productivity in Behavior Analysis: The Most Prolific Authors and Institutions from 1992 to 2001 - Shabani, Daniel B.; Carr, James E.; Petursdottir, Anna Ingeborg; Esch, Barbara E.; Gillett, Jill N. (The behavior analyst today, 2004)
Behavior analysis has matured as a discipline such that there are now over a dozen peer-reviewed journals devoted exclusively to its subject matter. In recent years, researchers have published with increasing frequency a number of bibliometric analyses in which journal content has been quantified and used as an index of research and publication practices in the field. The purpose of the current article was to identify the most prolific authors and institutions in behavior analysis from 1992 to 2001 by reviewing 10 journals that well represented its basic, applied, and conceptual/theoretical areas. The authors and affiliations of each of the articles included in our database were recorded, summed, and ranked. Results identified leading researchers and institutions in the discipline and demonstrated the breadth of journal outlets in which behavior analysts publish.